2021
DOI: 10.3389/fimmu.2021.637469
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the Tolerogenic Phenotype in the Liver by ImmTOR Nanoparticles

Abstract: ImmTOR biodegradable nanoparticles encapsulating rapamycin have been shown to induce a durable tolerogenic immune response to co-administered biologics and gene therapy vectors. Prior mechanism of action studies have demonstrated selective biodistribution of ImmTOR to the spleen and liver following intravenous (IV) administration. In the spleen, ImmTOR has been shown to induce tolerogenic dendritic cells and antigen-specific regulatory T cells and inhibit antigen-specific B cell activation. Splenectomy of mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…ImmTOR is a tolerogenic nanoparticle encapsulating rapamycin. [79][80][81][82] (B) A human, codon-optimized hMMUT mRNA encapsulated in a lipid nanoparticle. (C) The schematic of an AAV-mediated, nuclease-free genome editing vector and the integration and subsequent expression.…”
Section: Systemic Mrna Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…ImmTOR is a tolerogenic nanoparticle encapsulating rapamycin. [79][80][81][82] (B) A human, codon-optimized hMMUT mRNA encapsulated in a lipid nanoparticle. (C) The schematic of an AAV-mediated, nuclease-free genome editing vector and the integration and subsequent expression.…”
Section: Systemic Mrna Therapymentioning
confidence: 99%
“…AAV inverted terminal repeats (ITRs) flank a single‐stranded DNA sequence comprised of a promoter (either ubiquitous or tissue/liver‐specific), the MMUT transgene (either a mouse or human cDNA), and a polyA sequence. ImmTOR is a tolerogenic nanoparticle encapsulating rapamycin 79–82 . (B) A human, codon‐optimized hMMUT mRNA encapsulated in a lipid nanoparticle.…”
Section: Therapeutic Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in vitro studies have shown that rapamycin can also induce tolerogenic antigen presenting cells (APCs) which promote activation of regulatory T cells 11 . ImmTOR nanoparticles show selective biodistribution to the spleen and liver following intravenous administration where they are taken up by antigen-presenting cells (APCs) 9 , 12 14 . ImmTOR induces a tolerogenic phenotype in dendritic cells in the spleen 9 and in liver sinusoidal endothelial cells and other APCs in the liver 12 (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…ImmTOR nanoparticles show selective biodistribution to the spleen and liver following intravenous administration where they are taken up by antigen-presenting cells (APCs) 9 , 12 14 . ImmTOR induces a tolerogenic phenotype in dendritic cells in the spleen 9 and in liver sinusoidal endothelial cells and other APCs in the liver 12 (Fig. 1 ).…”
Section: Introductionmentioning
confidence: 99%